Digital Literacy as a Supporting Factor for Business Transformation of Coastal MSMEs in Makassar - Dian Indriani; Andi Irsandi Yusri (Jurnal Mirai Management, 2025)
This study aims to analyze the effect of digital literacy on business transformation among coastal Micro, Small, and Medium Enterprises (MSMEs) in Makassar City. The rapid development of digital technology has encouraged MSMEs to adapt to digital-based business systems in order to improve competitiveness and business sustainability. However, coastal MSMEs still face various challenges related to technology adoption, digital skills, and limited access to digital infrastructure. Therefore, digital literacy is considered an important factor in supporting business transformation in coastal economic sectors. This research employed a quantitative approach using a descriptive and explanatory research design. Data were collected through questionnaires distributed to 120 coastal MSME actors in Makassar City selected using purposive sampling techniques. The data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression analysis, t-tests, and coefficient of determination analysis with the assistance of SPSS software. The findings revealed that digital literacy has a positive and significant effect on business transformation among coastal MSMEs in Makassar City. The regression analysis showed a significance value of 0.000 and an R² value of 45.2%, indicating that digital literacy contributes substantially to improving digital marketing adoption, operational efficiency, innovation capability, customer engagement, and market expansion. This study highlights the importance of strengthening digital literacy to accelerate digital transformation and enhance the competitiveness of coastal MSMEs. Keywords: Digital literacy, business transformation, coastal MSMEs, digital transformation, Makassar City.